AVALIAÇÃO DE DESEMPENHO ZOOTÉCNICO DO PIAU CORRÓ (Leporinus lacustris) SOB DIFERENTES DENSIDADES DE ESTOCAGEM - SILVA, Maria Eduarda Vasconcelos Mendes1 (maendeszoo56@gmail.com); LEÃO, Fernanda Couto; ACUNHA, Rubia Mara Gomes; ALMEIDA, Rômulo Guilherme; COSTA, Deliane Cristina; CAMPOS, Cristiane Meldau de (ANAIS DO ENIC, 2023)
-